Clinical outcomes of kinesio taping applied in patients with knee osteoarthritis: A randomized controlled trial - (:unkn) unknown (IOS PRESS, 2017)
INTRODUCTION: The aim of this study was to compare kinesio taping along with conventional treatment to conventional treatment alone and to report the results of both a single and repetitive kinesio taping application applied on quadriceps femoris and hamstring muscles on pain, range of motion, muscle strength, and functional status in patients with knee osteoarthritis. METHODS: Fifty-four patients with knee osteoarthritis were randomly allocated to two groups. A total of 28 patients were included in kinesio taping group, others were included in the control group. Before and after intervention, pain was measured with visual analog scale, range of motion was measured with universal goniometer, muscle strength was measured with dynamometer, and functional status was measured with Knee Injury Osteoarthritis Outcome Score. RESULTS: There were statistically significant improvements in measures of pain, range of motion, quadriceps muscle strength and functional status between pre- and post-treatment in both groups (p < 0.05). In comparison, there were no significant differences with these parameters between groups (p > 0.05). It was also found that significant difference was observed in terms of range of motion, pain, functional status between pretreatment and post-taping in intervention group (p < 0.017). CONCLUSION: In conclusion, we could report that kinesio taping has significant immediate effects after a single kinesio taping application on range of motion, pain and functional status in patients with knee osteoarthritis. We could also report that KT in addition to conventional treatment is not superior to conventional treatment alone in terms of clinical outcomes over 3 weeks later.
Keywords: Kinesio taping; osteoarthritis; physiotherapy; MUSCLE STRENGTH; TURKISH VERSION; PAIN; HIP; QUADRICEPS; RELIABILITY; EFFICACY; INJURY; TAPE; RECOMMENDATIONS